Artwork by Syed Mohd. Bakar - Syed Mohd. Bakar (Wacana Seni Journal of Arts Discourse, 2008)
After a period of general activity, I turn to experimentation. I have already had a long, busy experience of painting behind me, so it is inevitable that I am no longer take influences from art which is the typical postmodern thing to do. I am deeply involved in irreality, that is the way I have always worked. First of all I am interested in people. I just love to look at faces, expressions, gestures, clothes and every facet of a human, either in action or in repose. I am interested in many things; mathematics and physics, all that stuff. So-called high art was never very important to me.